Pelatihan Dan Pendampingan Legalitas Usaha Melalui Aplikasi Online Single Submission Sebagai Wujud Pemberdayaan UMKM Desa Bareng, Kabupaten Jombang - Selvia Selvia; Nurul Azizah (Fakultas Teknik Universitas Cenderawasih, 2023)
Online Single Submission (OSS) is an application that functions to make business licenses or business legality online for both micro, medium and large scale businesses. As a form of empowering MSMEs in the Bareng Village, the authors carried out socialization activities regarding the importance of having a business legality or in this case a Business Identification Number (NIB) and also conducted a survey of every MSMEs actor in the Bareng Village. The purpose of this research is to make it easy for business owners to obtain capital assistance in the form of supporting or supporting tools, capital money, and business development funds. Apart from being used as a business identity, NIB ownership is what brings benefits to business owners. This study uses a qualitative method by surveying every MSMEs actor and also using a quantitative method. The results of this study explain that NIB can stimulate MSMEs products so that they have an identity to be recognized by the wider community so that they can prosper MSMEs actors and Become a Legal protector of business that are officil and recognized by the state throught the OSS or Online single submission.